Hubungan Praktik Sholat dengan Kesehatan Mental: Tinjauan dari Perspektif Psikologi dan Islam - Maghfira, Bhebyalna; Amiruddin, Muhammad; Salafi, Muchamad Asafin; Effendy, Maulina Rosalia (Maliki Interdisciplinary Journal, 2025)
This study reviews the relationship between the practice of ṣalāh (prayer) and mental health from the perspectives of modern psychology and Islamic values. A descriptive-narrative literature review was conducted, analyzing peer-reviewed studies and relevant scholarly reports published between 2020 and 2025. The findings indicate that regular, mindful prayer contributes to reductions in stress and anxiety, enhances inner calm, and strengthens psychological well-being through mechanisms such as emotion regulation, meaning-making, routine coping, and spiritual connectedness. Prayer also functions as a culturally consonant, non-pharmacological coping strategy within Muslim communities. However, the evidence is heterogeneous, and integration of religious elements into mental health practice requires culturally sensitive, evidence-based, and ethically guided approaches. Overall, consistent and reflective practice of ṣalāh can be considered a valuable component in promotive and preventive mental health efforts.